The Influence of the Inside Outside Circle Cooperative Learning Model on Students' Mathematical Communication Ability - Sarah, Kamai; Mursalin, Mursalin; Muliana, Muliana; Nuraina, Nuraina; Rohantizani, Rohantizani (International Journal for Educational and Vocational Studies, 2021)
Students' mathematical communication is stated to be low because students learn by listening and seeing the teacher solve mathematical problems and students have difficulty in expressing everyday events in mathematical models. This study aims to determine whether there is an influence of the Inside Outside Circle (IOC) type of cooperative learning model on students' mathematical communication skills better than using scientific learning. This study uses a quantitative approach with the type of research Quasi-Experimental Design and the design of this research The Nonequivalent Postets-Only Control Group Design. The population in this study were all students of class VIII SMP Negeri 1 Nisam, while the samples were class VIIIB as the experimental class and class VIII-A as the control class with the sampling technique of purposive sampling. The data collection technique in this study used a mathematical communication ability test. The data analysis was carried out for the mathematical communication ability test using the t-test because the data were normally distributed and homogeneous, the data were processed using SPSS 18 software and the hypothesis test results were obtained with a significant value of 0.000 less than 0.05, which means reject H0 and accept Ha. The results showed that there was an effect of the Inside-Outside Circle (IOC) type of cooperative learning model on students' mathematical communication skills.